Penggunaan Metode Project Based Learning (PjBL) dan Strategi Diferensiasi untuk Meningkatkan Hasil Belajar Pendidikan Pancasila Pada Siswa Kelas 5 di SDN Dukuh Menanggal - Prastyaningsih, Eka; Anindayati, Arista Tri; Fitriani, Fadilatul; Triningsih, Endah; Kholiqin, Ashfanul; Nurmala, Adisa Ika; Yustitia, Via; Rahayu, Daniar Meiliana (Indo-MathEdu Intellectuals Journal, 2025)
This research aims of this study is to use the Project Based Learning (PjBL) method and the differentiation strategy to improve Pancasila Education learning outcomes on the cooperation material between city/district government and the community in grade 5 students of SDN Dukuh Menanggal I/424 Surabaya in 2024/2025. The Project Based Learning (PjBL) method and the differentiation strategy are used to improve students' understanding by doing on projects through the differentiation. The collection methods used namely documentation method. The data analysis technique used is the descriptive percentage analysis technique. The percentage of learning outcome completion during the pre-cycle was 58%, cycle 1 was 82.75% and cycle 2 was 100%. The application of the Project Based Learning (PjBL) method and the differentiation strategy that have been carried out provide more optimal learning outcomes than during the pre-cycle. However, the application of the Project Based Learning (PjBL) method and the differentiation strategy are something that very challenging for teachers, because teachers must prepare a mature learning design to accommodate various characters of students in the classroom